Involving consumers in food product development: Perspectives on the application of circular food design - Sijtsema, Siet J.; Snoek, Harriette M. (Frontiers in Sustainable Food Systems, 2023)
Consumers and the food they choose, along with the actors providing this food, play a crucial role in the transformation toward a more sustainable food system. The circular food design model is a tool that supports consumer orientation in food product development and shows that it is not a static one-way direction but includes feedback loops and co-creative processes. In this study, circular food design was put into practice in two cases. Specifically, the following was explored: 1. how the application of circular food design can be done in different phases of product development, 2. how creativity and interaction can be stimulated, and 3. how different business disciplines that can be involved. Learnings from a series of workshops were described from company and consumer research perspectives. The results showed that to make consumer research valuable in this development process, there was a need for interaction in different ways, including focused consumer research and understanding by food production actors in an interactive and iterative process supported by a creative approach and visualizations, and with cooperation between different departments within companies. Using this interaction for combining consumer- and market-driven thinking delivers more tailored and technically feasible innovations with engagement among all actors.